Application of Financial Reports on Frozen Food SMEs Using Linear Sequential - Muhammad Arsyad Dhani; Uce Indahyanti (Procedia of Engineering and Life Science, 2022)
Planning in managing finances is needed by SMEs in order to be able to overcome a financial problem in everyday life. The existence of a financial report application no longer records in a book or paperless without the need to flip through the financial report book again to take notes. This financial report application provides a better overview and control of financial management, income, and life in general financially and provides information and meets the needs of financial management in SMEs in their operational activities. This study uses the method of a linear sequential development model, an approach to systematic and sequential software development that starts at the system level and progresses through analysis, design, coding, testing, and maintenance. As a result, web-based financial report applications can make it easier to provide information to the finance department. The financial report application works well in searching for money recording data and also in presenting information easily. Facilitates the process of processing financial records and making financial reports. The application is made web, so that in running this application the user requires a web browser.